Alceu Amoroso Lima e o regime militar, 1964-1968 - Sydow, Evanize Martins (2007)
This work seeks to analyze a brief, but rich period of Alceu Amoroso Lima ́s trajectory, who was also known by his nickname, Tristão Athayde, considered one of the principal catholic thinkers of century XX. The years between 1964 and 1968 come as an experience for what is called here as radicalism fase, when the writer, through weekly published articles in the Jornal do Brasil newspaper, severally criticizes the military regime established in 1964. During these years, the Politics, that always characterized his books and newspaper’s articles, sets the tone of everything which is written, together with the facts that highlighted the Catholic Church and the Brazilian society. The analysis of this research has been done based on the principal letters switched daily between the journalist and his daughter, Mother Superior Maria Teresa, and the articles published weekly in Jornal do Brasil newspaper. Also, interviews were realized with personalities that got along with Alceu, as some interviews offered by him were analyzed and therefore published in books.